Atomically resolved cementite dissolution governed by the strain state in pearlite steel wires. (November 2015) - Bang, Chan-Woo; Seol, Jae-Bok; Yang, Yo-Sep; Park, Chan-Gyung
Graphical abstract: Abstract: Atom probe tomography was performed to study cementite dissolution as a function of the strain state of pearlite colonies with respect to the applied external strain in severely drawn pearlite steels. We prove that the migration of carbon from cementite into ferrite in the colonies increases under iso-stress conditions relative to that under iso-strain conditions at strains above 1.26. Our findings indicate that the strain state is an important microstructural component that controls the carbon redistribution in steel wires. We propose that the carbon–dislocation interaction is likely to be more prevalent under iso-stress conditions than in the iso-strain state.